Teladan Orangtua dalam Pertumbuhan Rohani Anak Remaja - Milla Susanti; Malik Bambangan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This study examines how parents can serve as role models in fostering the spiritual growth of their adolescents. Parents play a fundamental role in shaping their children's character and faith by providing positive examples that adolescents can imitate in their daily lives. Spiritual growth during adolescence is particularly important because it serves as a strong foundation for their future faith, values, and moral development. The purpose of this study is to explore how parental role modeling influences adolescents' spiritual growth. This research employed a qualitative methodology using a library research approach. Relevant books, journal articles, theological literature, and other scholarly references were analyzed to examine theories and concepts related to parental roles and adolescent spiritual formation. The findings indicate that effective parental role modeling is demonstrated through words, behavior, love, faithfulness, integrity, and purity, which encourage adolescents to develop a deeper relationship with God and practice Christian values consistently. The study concludes that parents should actively model faith in everyday life as an essential part of educating their adolescents. By becoming living examples of Christian values, parents can significantly contribute to nurturing adolescents' spiritual maturity and strengthening their commitment to a lifelong life of faith.